A sequence { a i } i = 1 n has the property that S n = F n where S n = i = 1 ∑ n a i , F 1 = 1 , F 2 = 1 , and F n = F n − 1 + F n − 2 . The closed form of i = 1 ∑ n a 2 i − 1 can be represented as S f ( n ) + c where f ( n ) is a function of n and c is a constant. Find the last three digits of f ( 2 0 1 3 ) + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that ∑ k = 1 n F 2 k − 1 = F 2 n . We begin by noting the terms of a i :
a 1 = F 1 = 1
a 2 = F 2 − a 1 = 0
a 3 = F 3 − ( a 1 + a 2 ) = F 3 − F 2 = F 1
a 4 = F 4 − ( a 3 + a 2 + a 1 ) = F 4 − F 3 = F 2
Hence, a n + 2 = F n . Then, we have ∑ i = 1 n a 2 i − 1 = ∑ k = 1 n F 2 k − 3 . Because the Fibonacci numbers are (technically) not defined for negative arguments, we rewrite the first sum as a 1 + ∑ i = 2 n a 2 i − 1 in order to rewrite the latter as 1 + ∑ k = 2 n F 2 k − 3 = 1 + F 2 n − 2 as per the comment made at the beginning of the proof. Hence, ∑ i = 1 n a 2 i − 1 = S 2 n − 2 + 1 , and so f ( 2 0 1 3 ) + 1 = 2 ( 2 0 1 3 ) − 2 + 1 = 4 0 2 5 , whose last three digits are 0 2 5 .
Problem Loading...
Note Loading...
Set Loading...
Consider the criterion that ∑ k = 1 n a k = F n , then inductively, it better be the case that F n + 1 = F n + a n + 1 ⟹ a n + 1 = F n − 1 from the definition of F n + 1 . This suggests that for n > 2 , we can just set a n = F n − 2 (because this is when the recurrence hold); furthermore, we also need to set a 1 = F 1 , which leaves exactly one way to set a 2 = 0 . Of course, if we use the extended fibonacci sequence, then we can see that a n = F n − 2 .
Now, let's look at the summation: k = 1 ∑ n a 2 k − 1 = a 1 + a 3 + ⋯ + a 2 n − 1 = a 1 + a 3 ( a 1 + a 2 ) + a 5 ( a 3 + a 4 ) + ⋯ + a 2 n − 1 ( a 2 n − 3 + a 2 n − 2 ) = a 1 + k = 1 ∑ 2 n − 2 a k = a 1 + F 2 n − 2
Therefore, c = a 1 = 1 and f ( n ) = 2 n − 2 , which makes f ( 2 0 1 3 ) + c = 4 0 2 5 .